Concurso y arbitraje internacional - Gómez Jene, Miguel (CUADERNOS DE DERECHO TRANSNACIONAL, 2010)
Article 52 of The Spanih Insolvency Act takes a territorial approach to regulate the efficacy of the arbitral agreement in insolvency cases. Therefore, if the arbitral proceeding is being processed at the moment of the insolvency declaration, the arbitration will continue until the resolution of the arbitral award. However, if the arbitral proceeding is not yet being processed, the arbitral agreement in which the debtor is part is rendered ineffective through insolvency proceedings. This regulation raises two practical questions. The first and most important one deals with its own application in international cases: is it aplicable when the creditor has her habitual residence in a foreign country? The second question, which is important for internal matters, deals with the meaning of arbitral proceedings being processed. Both questions are studied in the following essay.
Keywords: International arbitration; Insolvency; New York Convention 1958; Genf Convention 1961; Arbitration Act; Insolvency Act; Arbitration agreement